Angiotensin‐converting enzyme inhibitors and risk of age‐related macular degeneration in individuals with hypertension. Issue 9 (11th May 2022) - Subramanian, Anuradhaa; Han, Diana; Braithwaite, Tasanee; Thayakaran, Rasiah; Zemedikun, Dawit T.; Gokhale, Krishna M.; Lee, Wen Hwa; Coker, Jesse; Keane, Pearse A.; Denniston, Alastair K.; Nirantharakumar, Krishnarajah; Azoulay, Laurent; et al.
Abstract : Aims: Several observational studies have examined the potential protective effect of angiotensin‐converting enzyme inhibitor (ACE‐I) use on the risk of age‐related macular degeneration (AMD) and have reported contradictory results owing to confounding and time‐related biases. We aimed to assess the risk of AMD in a base cohort of patients aged 40 years and above with hypertension among new users of ACE‐I compared to an active comparator cohort of new users of calcium channel blockers (CCB) using data obtained from IQVIA Medical Research Data, a primary care database in the UK. Methods: In this study, 53 832 and 43 106 new users of ACE‐I and CCB were included between 1995 and 2019, respectively. In an on‐treatment analysis, patients were followed up from the time of index drug initiation to the date of AMD diagnosis, loss to follow‐up, discontinuation or switch to the comparator drug. A comprehensive range of covariates were used to estimate propensity scores to weight and match new users of ACE‐I and CCB. Standardized mortality ratio weighted Cox proportional hazards model was used to estimate hazard ratios of developing AMD. Results: During a median follow‐up of 2 years (interquartile range 1–5 years), the incidence rate of AMD was 2.4 (95% confidence interval 2.2–2.6) and 2.2 (2.0–2.4) per 1000 person‐years among the weighted new users of ACE‐I and CCB, respectively. There was no association of ACE‐I use on the risk of AMD compared to CCB use in either the propensity score weighted or matched, on‐treatment analysis (adjusted hazard ratio: 1.07 [95% confidence interval 0.90–1.27] and 0.87 [0.71–1.07], respectively). Conclusion: We found no evidence that the use of ACE‐I is associated with risk of AMD in patients with hypertension.